2005
DOI: 10.1111/j.1365-2958.2005.04825.x
|View full text |Cite
|
Sign up to set email alerts
|

CsgA is a pathogen‐associated molecular pattern of Salmonella enterica serotype Typhimurium that is recognized by Toll‐like receptor 2

Abstract: SummaryKnowledge about the origin and identity of the microbial products recognized by the innate immune system is important for understanding the pathogenesis of inflammatory diseases. We investigated the potential role of Salmonella enterica serotype Typhimurium fimbriae as pathogen-associated molecular patterns (PAMPs) that may stimulate innate pathways of inflammation. We screened a panel of 11 mutants, each carrying a deletion of a different fimbrial operon, for their enteropathogenicity using the calf mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 64 publications
6
155
0
1
Order By: Relevance
“…It has been shown before that commensal E. coli strain are able to elicit a proinflammatory response [6, 56,58]. In this study, Recently, it has also been shown that curli fimbriae is a PAMP recognized by TLR2 [66]. In the system used in this study, no evidence for a PAMP function of curli fimbriae could be detected.…”
Section: Besides As Acting As a Physical Barrier The Intestinal Epithmentioning
confidence: 49%
“…It has been shown before that commensal E. coli strain are able to elicit a proinflammatory response [6, 56,58]. In this study, Recently, it has also been shown that curli fimbriae is a PAMP recognized by TLR2 [66]. In the system used in this study, no evidence for a PAMP function of curli fimbriae could be detected.…”
Section: Besides As Acting As a Physical Barrier The Intestinal Epithmentioning
confidence: 49%
“…BMDMs were differentiated as described previously (47). Briefly, femurs from three individual C57BL/6 TLR2-deficient and CD14-deficient mice were flushed, and a single cell suspension of the bone marrow was prepared in RPMI.…”
Section: Methodsmentioning
confidence: 99%
“…Tafi are essential for the formation of the extracellular matrix , which is involved in multicellular aggregation (Romling et al, 2000), pellicle formation (Collinson et al, 1993), biofilm formation (Austin et al, 1998;Gerstel & Romling, 2003;Prigent-Combaret et al, 2000;Vidal et al, 1998), environmental persistence , and adherence to plant tissues (Barak et al, 2005). Tafi also have pathogenesis-related properties in that they accelerate amyloidosis in mice (Lundmark et al, 2005), bind fibronectin (Arnqvist et al, 1992;Collinson et al, 1993;Olsen et al, 2002), are proinflammatory (Bian et al, 2000(Bian et al, , 2001Persson et al, 2003;Tukel et al, 2005), and enhance adherence and invasion of eukaryotic cells (Dibb-Fuller et al, 1999;Kim & Kim, 2004;La Ragione et al, 2000;Sukupolvi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%